Probing the influence of nonuniform Pt particle size distribution using a full three-dimensional, multiscale, multiphase polymer electrolyte membrane fuel cell model. (10th February 2022) - Choi, Jaeyoo; Kim, Eunsoo; Cha, Yohan; Ghasemi, Masoomeh; Ju, Hyunchul
Highlights: The result of various range of Pt particle size was compared with the constant size. PDF was used to randomly distribute Pt particles of different sizes to get a real CL. Numerical result for non-uniform Pt particles is consistent with experimental result. Abstract: Platinum (Pt) nanoparticles are used as an electrocatalyst in polymer electrolyte membrane (PEM) fuel cells. Visualization data of PEM fuel cell catalysts have shown that the size of Pt particles in the catalyst layer (CL) varies locally from several nanometers to tens of nanometers, owing to the agglomeration and degradation of Pt particles. Although many computational-fluid-dynamics-based PEM fuel cell modeling and simulation studies have been conducted, the majority of them have used the average value of the size of Pt particles owing to the complexity involved in considering the nonuniformity of the Pt particle size in the CL. In this study, we present a new approach to fuel cell CL modeling in PEM fuel cell simulations; the approach involves the consideration of various Pt particle size distributions. In the approach, a probability density function is used to randomly distribute Pt particles with different sizes in a computational domain under the assumption that the Pt particle size distribution follows a normal distribution curve. A sufficient number of grids, typically more than several million grid points, are used to obtain a Pt particle size distribution similar to that in a real CL. The new approach was applied to a comprehensive multiscale PEM fuel cell model and full three-dimensional fuel cell simulations were performed for different CL designs, Pt catalyst degradation levels, and operating conditions. Numerical simulation results clearly showed the significant effect of a nonuniform Pt particle size distribution on multidimensional contours of species concentration, temperature, and current density as well as the overall cell performance. Graphical abstract: Image, graphical abstract